Preliminary analyses reveal strong genetic structure in populations of Leucothoe vulgaris (Crustacea: Amphipoda: Leucothoidae) from Okinawa, Japan. Issue 1 (2nd January 2016) - White, Kristine N.; Reimer, James Davis; Lorion, Julien
Abstract : Preliminary phylogenetic analyses of specimens of a leucothoid amphipod, Leucothoe vulgaris, collected from sponges, ascidians, and coral rubble from Okinawa, Japan, were completed using mitochondrial COI and nuclear 18S ribosomal DNA sequences. Analyses of sequences from 83 specimens demonstrate that populations of L. vulgaris likely entail at least two cryptic species, which are reciprocally monophyletic and reproductively isolated. These two potentially cryptic species live in sympatry but are apparently morphologically identical, suggesting a geographically driven divergence process and secondary contact. Within each clade, two major subclades corresponding to the east and west coast of Okinawa Island were present, with divergence times of approximately 1.61–1.83 mya. This last result suggests a role of Pleistocene sea level changes in the current patterns of intra-specific genetic structure and highlights the need for a more comprehensive sampling of L. vulgaris throughout the Indo-west Pacific.